5-Metal-s-Triazolo-(3,4-b) Benzothiazole as an Antioxidant for Mustard Oil Stability - Deshmukh, M.V.; S. Deshpande, D.; Vaidya, N.G. (Asian Journal of Chemistry, 2010)
Studies on antioxidant property of 5-methyl-s-triazolo(3,4-b) benzothiazole towards the mustard oil stability was undertaken. The protection factor was calculated and the findings are discussed. In this communication, the effect of this azaheterocycle on the rancidity of mustard oil was compared with o-phenylene diamine and reported.